Pioglitazone treatment mitigates cardiovascular bioprosthetic degeneration in a chronic kidney disease model - Katahira, Shintaro; Barth, Mareike; Döpp, Robin; Sugimura, Yukiharu; Schmidt, Vera; Selig, Jessica Isabel; Saiki, Yoshikatsu; Jankowski, Joachim; Marx, Nikolaus; Jahnen-Dechent, Willi; Lichtenberg, Artur; Akhyari, Payam (Frontiers in Pharmacology, 2024)
Chronic kidney disease (CKD) is a risk factor for the development of cardiovascular diseases, e.g., atherosclerosis and calcific aortic valve disease, leading inevitably to valve replacement surgery. CKD patients with bioprosthetic cardiovascular grafts, in turn, have a higher risk of premature graft degeneration. Peroxisome proliferator-activated receptor gamma (PPARγ) activation by pioglitazone has cardio-renal protective properties, and research using a heterotopic valve implantation model has shown anti-degenerative effects of PPARγ activation on bioprosthetic valved grafts (BVG) in rats. The present work aims to analyze a potential protective effect of pioglitazone treatment on BVG in an adenine-induced rat model of CKD.BVG of Sprague Dawley rats were heterotopically implanted in Wistar rats in an infrarenal position for 4 and 8 weeks. Animals were distributed into three groups for each time point: 1) control group receiving standard chow, 2) CKD group receiving 0.25% adenine and 3) CKD+pioglitazone group (300 mg per kg of 0.25% adenine chow). BVG function was analyzed by echocardiography. Plasma analytes were determined and explanted grafts were analyzed by semi-quantitative real-time PCR, Western blot analysis, histology and immunohistology.PPARγ activation significantly reduced CKD-induced calcification of aortic and valvular segments of BVG by 44% and 53%, respectively. Pioglitazone treatment significantly also reduced CKD-induced intima hyperplasia by 60%. Plasma analysis revealed significantly attenuated potassium and phosphate levels after pioglitazone treatment. Moreover, PPARγ activation led to significantly decreased interleukin-6 gene expression (by 57%) in BVG compared to CKD animals. Pioglitazone treatment leads to functional improvement of BVG.This study broadens the understanding of the potential value of PPARγ activation in cardiorenal diseases and delineates pioglitazone treatment as a valuable option to prevent bioprosthetic graft failure in CKD. Further mechanistic studies, e.g., using small molecules activating PPARγ signaling pathways, are necessary for the evaluation of involved mechanisms. Additionally, the translation into pre-clinical studies using large animals is intended as the next research project.